2012
DOI: 10.1152/ajprenal.00512.2011
|View full text |Cite
|
Sign up to set email alerts
|

The PGE2-EP4 receptor is necessary for stimulation of the renin-angiotensin-aldosterone system in response to low dietary salt intake in vivo

Abstract: Increased cyclooxygenase-2 (COX-2) expression and PGE(2) synthesis have been shown to be prerequisites for renal renin release after Na(+) deprivation. To answer the question of whether EP4 receptor type of PGE(2) mediates renin regulation under a low-salt diet, we examined renin regulation in EP4(+/+), EP4(-/-), and in wild-type mice treated with EP4 receptor antagonist. After 2 wk of a low-salt diet (0.02% wt/wt NaCl), EP4(+/+) mice showed diminished Na(+) excretion, unchanged K(+) excretion, and reduced Ca(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
0
30
0
1
Order By: Relevance
“…80 Subsequently, a large body of experimental evidence demonstrated that PGE 2 derived from COX-2 serves as a dominant mechanism in mediating renin secretion from the JGA via EP 2 and EP 4 receptors which signal through the cAMP pathway. 81,82 Besides the JGA, the CD is another major site of both production and action of PGE 2 . Among the microdissected nephron segments, the highest amount of PGE 2 was detected in the CD.…”
Section: Pge 2 /Ep 4 Pathway As a Positivementioning
confidence: 99%
“…80 Subsequently, a large body of experimental evidence demonstrated that PGE 2 derived from COX-2 serves as a dominant mechanism in mediating renin secretion from the JGA via EP 2 and EP 4 receptors which signal through the cAMP pathway. 81,82 Besides the JGA, the CD is another major site of both production and action of PGE 2 . Among the microdissected nephron segments, the highest amount of PGE 2 was detected in the CD.…”
Section: Pge 2 /Ep 4 Pathway As a Positivementioning
confidence: 99%
“…This response appears to be mediated by cAMP-dependent hyperpolarization and inhibition of Ca 2+ currents that paradoxically inhibit renin-containing granule exocytosis. In vivo, low salt diet stimulates kidney renin mRNA levels and plasma renin concentrations in wild-type mice but not in EP4 knock-out mice or in mice treated with the EP4 antagonist ONO-AE3-208 (Poschke et al, 2012). Similar results were obtained in mice treated with furosemide (Nusing et al, 2005; Facemire et al, 2011).…”
Section: Kidneymentioning
confidence: 99%
“…In vivo, el aumento de la expresión de COX-2 y de la síntesis de prostaglandinas vasodilatadoras, en particular la PGE 2 y la PGI 2 , estimulan la liberación de renina. Ratones con deleción de los receptores EP2 -/-, EP4 -/e IP -/-, mostraron reducción significativa de la expresión de renina tras la administración de una dieta baja en NaCl durante una semana (30). Los receptores EP2, EP4e IP se acoplan a proteínas Gs y a la estimulación de la adenilato ciclasa 5 presente en las células secretoras de renina; la adenilato ciclasa cataliza la conversión de ATP en AMP cíclico (AMPc) que, a su vez, estimula la actividad de cinasas de proteínas como la PKA (31).…”
Section: R E G U L a C I ó N D E L A E X P R E S I ó N D E L A Cicloounclassified